Designing A Technological Business Model with A Strategic Entrepreneurship Approach in Public Organizations: A Survey of Tehran`s Municipality, Iran - Zahra Cheghaghasemi; Sepideh Kazemi (PT SOLUSI EDUKASI BERDIKARI, 2024)
The purpose of this article is to designing a technological business model with a strategic entrepreneurship approach in Municipality of Tehran Region 5. The research participants includes theoretical experts (university professors) and experimental experts (municipal managers). Theme analysis and MaxQDA software were used to identify the underlying categories of the technological business model with a strategic entrepreneurship approach. Also structural-interpretive modeling method and MicMac software were also used to identify the relationships between categories. Research findings showed that strategic entrepreneurship and entrepreneurial leadership have an impact on entrepreneurial orientation, entrepreneurial policy and entrepreneurial culture. These factors also affect technological entrepreneurship and urban entrepreneurship. Finally, technological entrepreneurship and urban entrepreneurship has significant impact on technological business.